2021
DOI: 10.1002/hed.26763
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between intraoral ultrasonographic and histopathological findings in patients with tongue cancer

Abstract: Background In this study, we aimed to investigate the relationships between histopathological and intraoral ultrasonographic (IUS) findings in patients with tongue cancer. Methods IUS and histopathological findings in 46 patients with tongue cancer were considered for this study. We assessed the relationships between IUS findings regarding tumor thickness, margin type, border type, and internal echo intensity; internal/peripheral Doppler findings; and muscle invasion and histopathological findings regarding tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Many previous studies have reported the relationship between intraoral ultrasonographic image characteristics in tongue cancer and late cervical lymph node metastasis, and intraoral ultrasonographic images were considered to best represent tongue cancer lesion characteristics. [5][6][7]11,26,30,31 Although intraoral ultrasonography is considered inferior to CT, MRI, and PET in terms of image reproducibility and operator dependence, the imaging conditions during intraoral ultrasonography were standardized, only B-mode images were used, and only one examiner with sufficient experience in intraoral ultrasonography collected imaging data. Therefore, we made every effort to obtain reproducible and stable images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies have reported the relationship between intraoral ultrasonographic image characteristics in tongue cancer and late cervical lymph node metastasis, and intraoral ultrasonographic images were considered to best represent tongue cancer lesion characteristics. [5][6][7]11,26,30,31 Although intraoral ultrasonography is considered inferior to CT, MRI, and PET in terms of image reproducibility and operator dependence, the imaging conditions during intraoral ultrasonography were standardized, only B-mode images were used, and only one examiner with sufficient experience in intraoral ultrasonography collected imaging data. Therefore, we made every effort to obtain reproducible and stable images.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the usefulness of intraoral ultrasonography in the evaluation of tongue cancer. [5][6][7][8][9][10][11] Lesion length, thickness, depth of invasion, and margins are reported factors associated with late cervical lymph node metastasis, and intraoral ultrasonographic images may contain features related to tongue cancer prognosis. 5,7,11 Although various studies have reported cervical lymph node metastasis in patients with tongue cancer, insufficient evidence is available to determine whether prophylactic dissection should be performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[4][5][6] Furthermore, the relationship between intraoral ultrasonographic images and late cervical lymph node metastasis has been shown. [7][8][9][10] This technique has also been used in measuring the depth of tongue cancer. [11][12][13] However, few studies have reported on the examination of common submucosal intraoral benign lesions, such as hemangiomas, irritation fibromas, mucous cysts, lipomas, and pleomorphic adenomas, using ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described the use of intraoral ultrasonography, and the usefulness of intraoral ultrasonography for tongue cancer has been reported 1,4–6 . Furthermore, the relationship between intraoral ultrasonographic images and late cervical lymph node metastasis has been shown 7–10 . This technique has also been used in measuring the depth of tongue cancer 11–13 .…”
Section: Introductionmentioning
confidence: 99%